The genome sequence of Cory’s shearwater, Calonectris borealis (Cory, 1881) [version 1; peer review: 2 approved] - Joan Ferrer Obiol; Guillem Izquierdo Arànega; Marta Riutort León; Raül Ramos Garcia; Jacob González-Solís Bou; Julio Rozas Liras (Wellcome Open Research)
We present a genome assembly from an individual female Calonectris borealis (Cory’s shearwater; Chordata; Aves; Procellariiformes; Procellariidae). The haplotype-resolved assembly contains two haplotypes with total lengths of 1,366.19 megabases and 1,211.47 megabases, respectively. Most of the assembly for haplotype 1 is scaffolded into 41 chromosomal pseudomolecules, including the Z and W sex chromosomes. Haplotype 2 has 39 autosomes. The mitochondrial genome has also been assembled and is 19.95 kilobases in length.